An Electrochemical Immunosensor for the Detection of B-Type Natriuretic Peptide (BNP) Based on Sandwich ELISA Using Screen Printed Carbon Electrodes - Yeni Wahyuni Hartati; Muhammad Hilman Daniswara; Ratna Nurmalasari; Shabarni Gaffar; Toto Subroto (Universitas Jenderal Soedirman, 2018)
B-type natriuretic peptide (BNP) is a 32-amino acid polypeptide, a cardiac neuro hormone that specifically secreted from heart ventricle as a response towards the increase of volume and pressure in the heart. The determination of BNP concentration in patients blood is one of the method used to diagnose heart failure. An electrochemical immunosensor modified with the streptavidin/biotin system on screen printed carbon electrodes for the detection of the BNP antigen was developed in this study. Monoclonal anti-BNP capture antibody was immobilized on streptavidin-modified SPCEs to give a well oriented of antibody. Furthermore, a biotinylated anti-BNP that conjugated with horseradish peroxidase (HRP) was used as secondary antibody. The electrochemical signal produced by redox activity of substrate 3,3,5,5'-tetramethybezidine dihydrochloride (TMB/H2O2) was measured by differential pulse voltammetry. The BNP immunosensor showed a linear response between 1.0×10-2 and 1.0×102 ng/mL, and the limit of detection was 3.3 ng/mL. BNP immunosensor is a promising technology for the rapid and convenient detection of heart failure.